If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -4 = 35 + -6y Reorder the terms: -4 + 4y = 35 + -6y Solving -4 + 4y = 35 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. -4 + 4y + 6y = 35 + -6y + 6y Combine like terms: 4y + 6y = 10y -4 + 10y = 35 + -6y + 6y Combine like terms: -6y + 6y = 0 -4 + 10y = 35 + 0 -4 + 10y = 35 Add '4' to each side of the equation. -4 + 4 + 10y = 35 + 4 Combine like terms: -4 + 4 = 0 0 + 10y = 35 + 4 10y = 35 + 4 Combine like terms: 35 + 4 = 39 10y = 39 Divide each side by '10'. y = 3.9 Simplifying y = 3.9
| z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 | | X=-0.5x+3 | | -7(2t+8)=-126 | | r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 |